Intracellular persister: A stealth agent recalcitrant to antibiotics - Personnic, Nicolas; Doublet, Patricia; Jarraud, Sophie (Frontiers in Cellular and Infection Microbiology, 2023)
The bulk of bacteria transiently evading appropriate antibiotic regimes and recovered from non-resolutive infections are commonly refer to as persisters. In this mini-review, we discuss how antibiotic persisters stem from the interplay between the pathogen and the cellular defenses mechanisms and its underlying heterogeneity.